Bioluminescent fungus Roridomyces viridiluminus sp. nov. and the first Chinese record of the genus Roridomyces, from Southwestern China - Dauner, Lucas A.p.; Karunarathna, Samantha C.; Tibpromma, Saowaluck; Xu, Jianchu; Mortimer, Peter E. (Phytotaxa, 2021)
A bioluminescent macrofungus found growing on dead wood in the mountains of Southwest China, Yunnan Province, Yulong Naxi Autonomous County, is analyzed and described. Phylogenetic analyses of the nuclear ribosomal large subunit (LSU) and internal transcribed spacer (ITS) gene regions place the fungus within the genus Roridomyces and confirm it to be a previously undescribed taxon. Morphological features support phylogenetic conclusions and include a glutinous stipe, a light yellowish-brown to beige or white pileus, and luminescent mycelium. Comprehensive descriptions, macro- and microscopic photographs, and phylogenetic trees are provided, as well as a table containing morphology and distribution of all Roridomyces taxa to aid in species identification and comparison. This is the first member of the genus Roridomyces to be identified in China.